Antifungal Resistance Pattern in Candida Species: Tackling the Emerging Threat to Human Health - Kainthola, Kanchan; Bisht, Dakshina; Bansal, Jagriti; Goel, Dr Varun; Rawat, Ashutosh; Rashmi, Rashmi (Journal of Neonatal Surgery, 2025)
Background: Candida is yeast like fungus and a normal commensal flora of human body but may be associated with superficial and deep seated fungal infections. C.albicans is the most common causative agent of candidiasis; the frequency of other Non-Albicans Candida (NAC) species is increasing. Material and Methods: Samples were processed and identified by standard microbiological methods candida species were isolated from various clinical. Species level identification and Antifungal susceptibility testing was done by using VITEK 2 compact system. Susceptibility was determined using an AST-YS09card, which tests the MIC of 6 antifungals, i.e., FLU, 5-FC, VRC, AMB, CAS, and MFG. Result: All total 438 isolates of different candida species were identified. Among those isolates, C.albicans found the most that is 34%, followed by C.tropicalis(23%), C.haemulonii(16%), C.krusei(10%), C.glabrata(7%), C.auris(6%), and C.parapsilosis(4%) respectively. Gender predominance of Candidiasis infection was seen in males (67%). Antifungal susceptibility profile of candida albicans shows maximum resistance to flucytosine(38%), followed by fluconazole(26%), caspofungin(20%), micafungin(16%), amphotericin B(13%), voriconazole(12%) respectively. Conclusion: Conclusion: Our study shows an increased incidence of Non albicans Candida over C.albicans showing a significant resistance against various antifungals. There is definitely a need to have a program to monitor the use of antifungals and preventive control measures taken to hinder the further dissemination of antifungals